Combined method for die compensation in sheet metal forming - Muhammad Marhaban, Agus Dwi Anggono (2014)
Sheet metal forming is one of the prominent methods to convert blank sheet material into a product. In sheet metal forming, proper allowance of its tools must be given to the elastic recovery, due to the nature of elastic property which is called springback. When stamped sheet components are removed from the forming tools, the internal stresses will rest, and a new equilibrium state will be reached. As a result, the final shape of the drawn part will deviate from the shape imposed by the forming tool. Therefore, it is very important that springback be accurately predicted and compensated. In the industry, this is a costly and time consuming process of product shaping and redesigning the tools manually. The goal of this research is to develop a compensation procedure that can perform this optimization process, using the combination of Displacement Adjustment (DA) and Spring Forward (SF) methods. Both are based on an iterative procedure. The method is needed for guiding die design to compensate for springback in a backward direction and then to compensate springback in a forward direction. This new approach is then called Combined Method for Die Compensation (CMDC). The testing of CMDC has been conducted in 2D model of U-bending and 3D shape of S-rail model adopted from Numisheet 2008. The result shows that CMDC is able to reduce error in every cycle of the total five cycles. The result of reduction in shape deviation is 66% to 73% for the 2D model compensation, and for the 3D model, 55% reduction in shape deviation can be reached. The CMDC method can be further implemented and integrated in a commercial FEM software to assist the optimization process to improve the precision of stamping products.